Anisotropic time-domain electronic response in cuprates driven by midinfrared pulses - Giusti, Francesca; Montanaro, Angela; Marciniak, Alexandre; Randi, Francesco; Boschini, Fabio; Glerean, Filippo; Jarc, G.; Eisaki, H.; Greven, M.; Damascelli, A.; Avella, Adolfo; Fausti, Daniele (Physical Review B, 2021)
Superconductivity in the cuprates is characterized by an anisotropic electronic gap of d-wave symmetry. The aim of this work is to understand how this anisotropy affects the nonequilibrium electronic response of high-Tc superconductors. Here we use a polarization selective time domain experiment to address the dynamics of electronic excitation of different symmetry in optimally doped Bi2Sr2Y0.08Ca0.92Cu2O8+δ and measure the nodal and antinodal nonequilibrium response resulting from photoexcitations with ultrashort pulses with photon energy comparable to the superconducting gap. The response to long wavelength photoexcitation with pump polarization along the Cu-Cu axis of the sample is discussed with the support of an effective d-wave BCS model which suggests that such transient response could be ascribed to an increase of pair coherence in the antinodal region.
CRIS-Team Scopus Importer:2022-07-20

Anomalous non-equilibrium response in black phosphorus to sub-gap mid-infrared excitation - Montanaro, Angela; Giusti, Francesca; Zanfrognini, Matteo; Di Pietro, Paola; Glerean, Filippo; Jarc, Giacomo; Rigoni, Enrico Maria; Mathengattil, Shahla Y.; Varsano, Daniele; Rontani, Massimo; Perucchi, Andrea; Molinari, Elisa; et al. (Nature Communications, 2022)
The competition between the electron-hole Coulomb attraction and the 3D dielectric screening dictates the optical properties of layered semiconductors. In low-dimensional materials, the equilibrium dielectric environment can be significantly altered by the ultrafast excitation of photo-carriers, leading to renormalized band gap and exciton binding energies. Recently, black phosphorus emerged as a 2D material with strongly layer-dependent electronic properties. Here, we resolve the response of bulk black phosphorus to mid-infrared pulses tuned across the band gap. We find that, while above-gap excitation leads to a broadband light-induced transparency, sub-gap pulses drive an anomalous response, peaked at the single-layer exciton resonance. With the support of DFT calculations, we tentatively ascribe this experimental evidence to a non-adiabatic modification of the screening environment. Our work heralds the non-adiabatic optical manipulation of the electronic properties of 2D materials, which is of great relevance for the engineering of versatile van der Waals materials.
CRIS-Team Scopus Importer:2022-07-20

Cavity-mediated thermal control of metal-to-insulator transition in 1T-TaS2 - Jarc, Giacomo; Mathengattil, Shahla Yasmin; Montanaro, Angela; Giusti, Francesca; Rigoni, Enrico Maria; Sergo, Rudi; Fassioli Olsen, Francesca; Winnerl, Stephan; Dal Zilio, Simone; Mihailovic, Dragan; Prelovšek, Peter; Eckstein, Martin; et al. (Nature, 2023)
Placing quantum materials into optical cavities provides a unique platform for controlling quantum cooperative properties of matter, by both weak and strong light–matter coupling1,2. Here we report experimental evidence of reversible cavity control of a metal-to-insulator phase transition in a correlated solid-state material. We embed the charge density wave material 1T-TaS2 into cryogenic tunable terahertz cavities3 and show that a switch between conductive and insulating behaviours, associated with a large change in the sample temperature, is obtained by mechanically tuning the distance between the cavity mirrors and their alignment. The large thermal modification observed is indicative of a Purcell-like scenario in which the spectral profile of the cavity modifies the energy exchange between the material and the external electromagnetic field. Our findings provide opportunities for controlling the thermodynamics and macroscopic transport properties of quantum materials by engineering their electromagnetic environment.
CRIS-Team Scopus Importer:2023-10-27

Dynamics of nonthermal states in optimally doped B⁢i2⁢S⁢r2⁢C⁢a0.92⁢Y0.08⁢C⁢u2⁢O8+ẟ revealed by midinfrared three-pulse spectroscopy - Montanaro, Angela; Rigoni, Enrico Maria; Giusti, Francesca; Barba, Luisa; Chita, Giuseppe; Glerean, Filippo; Jarc, Giacomo; Mathengattil, Shahla Y.; Boschini, Fabio; Eisaki, Hiroshi; Greven, Martin; Damascelli, Andrea; et al. (Physical Review B, 2024)
In the cuprates, the opening of a d-wave superconducting (SC) gap is accompanied by a redistribution of spectral weight at energies two orders of magnitude larger than this gap. This indicates the importance to the pairing mechanism of on-site electronic excitations, such as orbital transitions or charge transfer excitations. Here, we resort to a three-pulse pump-probe scheme to study the broadband nonequilibrium dielectric function in optimally doped Bi2Sr2Ca0.92Y0.08Cu2O8+δ and we identify an interband excitation peaked at 2 eV whose spectral weight is transiently modified by the pump. Photoexcitation with near-infrared and midinfrared pulses, with photon energies, respectively, above and below the SC gap, reveals that the spectral weight dynamics is different for different pump wavelengths and depends on the time order of the two photoexcitations. The picture that emerges is that, while high-energy pulses excite quasiparticles in both nodal and thermally inaccessible antinodal states, photoexcitation by low-energy pulses mostly accelerates the condensate and creates excitations predominantly at the nodes of the SC gap. These results, rationalized by simulations based on the kinetic equations for d-wave superconducting gaps, indicate that dynamical control of the momentum-dependent distribution of nonthermal quasiparticles may be achieved by the selective tuning of the photoexcitation.
CRIS-Team Scopus Importer:2024-09-20
Keywords: Dynamical phase transitions; Pairing mechanisms; Photoinduced effect; Ultrafast phenomena; Quantum many-body systems; Superconductivity; Drude model; Femtosecond laser spectroscopy; Optical pumping; Symmetries in condensed matter; Time-resolved infrared spectroscopy; Ultrafast pump-probe spectroscopy

Femtosecond covariance spectroscopy - Tollerud, Jonathan Owen; Sparapassi, Giorgia; Montanaro, Angela; Asban, Shahaf; Glerean, Filippo; Giusti, Francesca; Marciniak, Alexandre; Kourousias, George; Bille, Fulvio; Cilento, Federico; Mukamel, Shaul; Fausti, Daniele (Proceedings of the National Academy of Sciences of the United States of America, 2019)
The success of nonlinear optics relies largely on pulse-to-pulse consistency. In contrast, covariance-based techniques used in photoionization electron spectroscopy and mass spectrometry have shown that a wealth of information can be extracted from noise that is lost when averaging multiple measurements. Here, we apply covariance-based detection to nonlinear optical spectroscopy, and show that noise in a femtosecond laser is not necessarily a liability to be mitigated, but can act as a unique and powerful asset. As a proof of principle we apply this approach to the process of stimulated Raman scattering in α-quartz. Our results demonstrate how nonlinear processes in the sample can encode correlations between the spectral components of ultrashort pulses with uncorrelated stochastic fluctuations. This in turn provides richer information compared with the standard nonlinear optics techniques that are based on averages over many repetitions with well-behaved laser pulses. These proof-of-principle results suggest that covariance-based nonlinear spectroscopy will improve the applicability of fs nonlinear spectroscopy in wavelength ranges where stable, transform-limited pulses are not available, such as X-ray free-electron lasers which naturally have spectrally noisy pulses ideally suited for this approach.
CRIS-Team Scopus Importer:2022-07-20
Keywords: Impulsive stimulated scattering; Stochastic light; Ultrafast spectroscopy

Free electron laser stochastic spectroscopy revealing silicon bond softening dynamics - De Angelis, Dario; Principi, Emiliano; Bencivenga, Filippo; Fausti, Daniele; Foglia, Laura; Klein, Yishay; Manfredda, Michele; Mincigrucci, Riccardo; Montanaro, Angela; Pedersoli, Emanuele; Pelli Cresi, Jacopo Stefano; Perosa, Giovanni; et al. (Physical Review B, 2023)
Time-resolved x-ray emission/absorption spectroscopy (Tr-XES/XAS) is an informative experimental tool sensitive to electronic dynamics in materials, widely exploited in diverse research fields. Typically, Tr-XES/XAS requires x-ray pulses with both a narrow bandwidth and subpicosecond pulse duration, a combination that in principle finds its optimum with Fourier transform-limited pulses. In this work, we explore an alternative experimental approach, capable of simultaneously retrieving information about unoccupied (XAS) and occupied (XES) states from the stochastic fluctuations of broadband extreme ultraviolet pulses of a free electron laser. We used this method, in combination with singular-value decomposition and Tikhonov regularization procedures, to determine the XAS/XES response from a crystalline silicon sample at the L2,3 edge, with an energy resolution of a few tens of meV. Finally, we combined this spectroscopic method with a pump-probe approach to measure structural and electronic dynamics of a silicon membrane. Tr-XAS/XES data obtained after photoexcitation with an optical laser pulse at 390 nm allowed us to observe perturbations of the band structure, which are compatible with the formation of the predicted precursor state of a nonthermal solid-liquid phase transition associated with a bond softening phenomenon.
CRIS-Team Scopus Importer:2023-08-04

Manipulation of Charge Delocalization in a Bulk Heterojunction Material Using a Mid-Infrared Push Pulse - Montanaro, Angela; Park, Kyu Hyung; Fassioli Olsen, Francesca; Giusti, Francesca; Fausti, Daniele; Scholes, Gregory D. (Journal of Physical Chemistry C, 2023)
In organic bulk heterojunction materials, charge delocalization has been proposed to play a vital role in the generation of free carriers by effectively reducing the Coulomb attraction via an interfacial charge transfer exciton (CTX). Pump-push-probe (PPP) experiments produced evidence that the excess energy given by a push pulse enhances delocalization, thereby increasing photocurrent. However, previous studies have employed near-infrared push pulses in the range ∼0.4–0.6 eV, which is larger than the binding energy of a typical CTX. This raises the doubt that the push pulse may directly promote dissociation without involving delocalized states. Here, we perform PPP experiments with mid-infrared push pulses at energies that are well below the binding energy of a CTX state (0.12–0.25 eV). We identify three types of CTXs: delocalized, localized, and trapped. The excitation resides over multiple polymer chains in delocalized CTXs, while it is restricted to a single chain (albeit maintaining a degree of intrachain delocalization) in localized CTXs. Trapped CTXs are instead completely localized. The pump pulse generates a “hot” delocalized CTX, which promptly relaxes to a localized CTX and eventually to trapped states. We find that photo-exciting localized CTXs with push pulses resonant to the mid-infrared charge transfer absorption can promote delocalization and, in turn, contribute to the formation of long-lived charge separated states. On the other hand, we found that trapped CTXs are non-responsive to the push pulses. We hypothesize that delocalized states identified in prior studies are only accessible in systems where there is significant interchain electronic coupling or regioregularity that supports either inter- or intrachain polaron delocalization. This, in turn, emphasizes the importance of engineering the micromorphology and energetics of the donor–acceptor interface to exploit the full potential of a material for photovoltaic application
Keywords: Absorption; Charge transfer; Energy; Excitons; Polarons

Multimode vibrational coupling across the insulator-to-metal transition in 1T-TaS2 in THz cavities - Jarc, Giacomo; Mathengattil, Shahla Yasmin; Montanaro, Angela; Rigoni, Enrico; Dal Zilio, Simone; Fausti, Daniele (Journal of Chemical Physics, 2024)
The use of optical cavities on resonance with material excitations allows controlling light-matter interaction in both the regimes of weak and strong coupling. We study here the multimode vibrational coupling of low energy phonons in the charge-density-wave material 1T-TaS2 across its insulator-to-metal phase transition. For this purpose, we embed 1T-TaS2 into THz Fabry-Pérot cryogenic cavities tunable in frequency within the spectral range of the vibrational modes of the insulating phase and track the linear response of the coupled phonons across the insulator-to-metal transition. In the low temperature dielectric state, we reveal the signatures of a multimode vibrational strong collective coupling. The observed polariton modes inherit character from all the vibrational resonances as a consequence of the cavity-mediated hybridization. We reveal that the vibrational strong collective coupling is suppressed across the insulator-to-metal transition as a consequence of the phonon-screening induced by the free charges. Our findings emphasize how the response of cavity-coupled vibrations can be modified by the presence of free charges, uncovering a new direction toward the tuning of coherent light-matter interaction in cavity-confined correlated materials.
CRIS-Team Scopus Importer:2024-10-25
Keywords: Coupled oscillators; Phase transitions; Phonons; Quasiparticle; Terahertz radiation; Linear response; Optical cavity

Terahertz saturable absorption from relativistic high-temperature thermodynamics in black phosphorus - Adhlakha, Nidhi; Ebrahimpour, Zeinab; Di Pietro, Paola; Schmidt, Johannes; Piccirilli, Federica; Fausti, Daniele; Montanaro, Angela; Cappelluti, Emmanuele; Lupi, Stefano; Perucchi, Andrea (Physical Review Applied, 2023)
Due to its tunable infrared band gap and its anisotropic conduction properties, black phosphorus represents a very unique two-dimensional (2D) material, the potential of which in the engineering of new devices still needs to be fully explored. Here, we investigate the nonlinear terahertz (THz) electrodynamics of black phosphorus along the more conducting armchair direction. Similarly to the case of other 2D systems such as graphene and topological insulators, the THz saturable-absorption properties of black phosphorus can be understood within a thermodynamic model by assuming a fast thermalization of the electron bath. While black phosphorus does not display the presence of massless fermions at ambient pressure and temperature, our analysis shows that its anomalous THz nonlinear properties can be accounted for by a relativistic massive Dirac dispersion, provided that the Fermi temperature is low enough. An optimal tuning of the Fermi level therefore represents a strategy to engineer a strong THz nonlinear response in other massive Dirac materials, such as transition-metal dichalchogenides or high-temperature superconductor
CRIS-Team Scopus Importer:2023-12-01
Keywords: Nonlinear optics; Optoelectronics; Dirac semimetal; Elemental semiconductors; Multilayer thin films; Phosphorene; Van der Waals systems; Terahertz spectroscopy

Time-resolved multimode heterodyne detection for dissecting coherent states of matter - Glerean, Filippo; Jarc, Giacomo; Marciniak, Alexandre; Giusti, Francesca; Sparapassi, Giorgia; Montanaro, Angela; Rigoni, Enrico Maria; Tollerud, Jonathan Owen; Fausti, Daniele (Optics Letters, 2020)
Unveiling and controlling the time evolution of the momentum and position of low energy excitations such as phonons, magnons, and electronic excitation is the key to attain coherently driven new functionalities of materials. Here we report the implementation of femtosecond time- and frequency-resolved multimode heterodyne detection and show that it allows for independent measurement of the time evolution of the position and momentum of the atoms in coherent vibrational states in α-quartz. The time dependence of the probe field quadratures reveals that their amplitude is maximally changed when the atoms have maximum momentum, while their phase encodes a different information and evolves proportionally to the instantaneous atomic positon. We stress that this methodology, providing the mean to map both momentum and position in one optical observable, may be of relevance for both quantum information technologies and time-domain studies on complex materials.
CRIS-Team Scopus Importer:2022-07-20

Transient measurement of phononic states with covariance-based stochastic spectroscopy - Sparapassi, Giorgia; Cavaletto, Stefano M.; Tollerud, Jonathan; Montanaro, Angela; Glerean, Filippo; Marciniak, Alexandre; Giusti, Fancesca; Mukamel, Shaul; Fausti, Daniele (Light: Science & Applications, 2022)
We present a novel approach to transient Raman spectroscopy, which combines stochastic probe pulses and a covariance-based detection to measure stimulated Raman signals in alpha-quartz. A coherent broadband pump is used to simultaneously impulsively excite a range of different phonon modes, and the phase, amplitude, and energy of each mode are independently recovered as a function of the pump–probe delay by a noisy-probe and covariance-based analysis. Our experimental results and the associated theoretical description demonstrate the feasibility of 2D-Raman experiments based on the stochastic-probe schemes, with new capabilities not available in equivalent mean-value-based 2D-Raman techniques. This work unlocks the gate for nonlinear spectroscopies to capitalize on the information hidden within the noise and overlooked by a mean-value analysis.
CRIS-Team Scopus Importer:2022-07-20

Tunable cryogenic terahertz cavity for strong light-matter coupling in complex materials - Jarc, Giacomo; Mathengattil, Shahla Yasmin; Giusti, Francesca; Barnaba, Maurizio; Singh, Abhishek; Montanaro, Angela; Glerean, Filippo; Rigoni, Enrico Maria; Dal Zilio, Simone; Winnerl, Stephan; Fausti, Daniele (Review of Scientific Instruments, 2022)
We report here the realization and commissioning of an experiment dedicated to the study of the optical properties of light-matter hybrids constituted of crystalline samples embedded in an optical cavity. The experimental assembly developed offers the unique opportunity to study the weak and strong coupling regimes between a tunable optical cavity in cryogenic environment and low energy degrees of freedom, such as phonons, magnons, or charge fluctuations. We describe here the setup developed that allows for the positioning of crystalline samples in an optical cavity of different quality factors, the tuning of the cavity length at cryogenic temperatures, and its optical characterization with a broadband time domain THz spectrometer (0.2-6 THz). We demonstrate the versatility of the setup by studying the vibrational strong coupling in CuGeO3 single crystal at cryogenic temperatures.
CRIS-Team Scopus Importer:2022-07-20

Ultrafast Dynamics of the Topological Semimetal GdSbxTe2-x-δ in the Presence and Absence of a Charge Density Wave - Kirby, Robert J.; Montanaro, Angela; Giusti, Francesca; Koch-Liston, Andre; Lei, Shiming; Petrides, Ioannis; Narang, Prineha; Burch, Kenneth S.; Fausti, Daniele; Scholes, Gregory D.; Schoop, Leslie M. (Journal of Physical Chemistry C, 2023)
Time-resolved dynamics in charge-density-wave materials have revealed interesting out-of-equilibrium electronic responses. However, these are typically only performed in a single material possessing a CDW. As such, it is challenging to separate subtle effects originating from the CDW. Here, we report on the ultrafast dynamics of the GdSbxTe2-x-δ series of materials where EF can be tuned, resulting in a change from an undistorted tetraganal phase to a CDW with a wavevector that depends on x. Using mid-infrared, near-infrared, and visible excitation, we find the dynamics are sensitive to both EF and the presence of the CDW. Specifically, as the Sb content of the compounds increases, transient spectral features shift to higher probe energies. In addition, we observe an enhanced lifetime and change in the sign of the transient signal upon removing the CDW with high Sb concentrations. Finally, we reveal fluence- and temperature-dependent photoinduced responses of the differential reflectivity, which provide evidence of transient charge density wave suppression in related telluride materials. Taken together our results provide a blueprint for future ultrafast studies of CDW systems.
CRIS-Team Scopus Importer:2023-01-27

Ultrafast pump-probe phase-randomized tomography - Glerean, Filippo; Rigoni, Enrico Maria; Jarc, Giacomo; Mathengattil, Shahla Yasmin; Montanaro, Angela; Giusti, Francesca; Mitrano, Matteo; Benatti, Fabio; Fausti, Daniele (Light: Science & Applications, 2025)
Measuring fluctuations in matter’s low-energy excitations is the key to unveiling the nature of the non-equilibrium response of materials. A promising outlook in this respect is offered by spectroscopic methods that address matter fluctuations by exploiting the statistical nature of light-matter interactions with weak few-photon probes. Here we report the first implementation of ultrafast phase randomized tomography, combining pump-probe experiments with quantum optical state tomography, to measure the ultrafast non-equilibrium dynamics in complex materials. Our approach utilizes a time-resolved multimode heterodyne detection scheme with phase-randomized coherent ultrashort laser pulses, overcoming the limitations of phase-stable configurations and enabling a robust reconstruction of the statistical distribution of phase-averaged optical observables. This methodology is validated by measuring the coherent phonon response in α-quartz. By tracking the dynamics of the shot-noise limited photon number distribution of few-photon probes with ultrafast resolution, our results set an upper limit to the non-classical features of phononic state in α-quartz and provide a pathway to access non-equilibrium quantum fluctuations in more complex quantum material

Visible pump-mid infrared pump-broadband probe: Development and characterization of a three-pulse setup for single-shot ultrafast spectroscopy at 50 kHz - Montanaro, Angela; Giusti, Francesca; Colja, Matija; Brajnik, Gabriele; Marciniak, Alexandre M. A.; Sergo, Rudi; De Angelis, Dario; Glerean, Filippo; Sparapassi, Giorgia; Jarc, Giacomo; Carrato, Sergio; Cautero, Giuseppe; et al. (Review of Scientific Instruments, 2020)
We report here an experimental setup to perform three-pulse pump-probe measurements over a wide wavelength and temperature range. By combining two pump pulses in the visible (650 nm-900 nm) and mid-IR (5 μm-20 μm) range, with a broadband supercontinuum white-light probe, our apparatus enables both the combined selective excitation of different material degrees of freedom and a full time-dependent reconstruction of the non-equilibrium dielectric function of the sample. We describe here the optical setup, the cryogenic sample environment, and the custom-made acquisition electronics capable of referenced single-pulse detection of broadband spectra at the maximum repetition rate of 50 kHz, achieving a sensitivity of the order of 10-4 over an integration time of 1 s. We demonstrate the performance of the setup by reporting data on a mid-IR pump, optical push, and broadband probe in a single crystal of Bi2Sr2Y0.08Ca0.92Cu2O8+δ across the superconducting and pseudogap phases.
CRIS-Team Scopus Importer:2022-07-20